Demokrasi dan Kebudayaan Jawa: Studi Kasus Dilema Keberlangsungan Pelaksanaan Demokrasi di Yogyakarta - Nugraha, Mauludy; Valentia, Paskah; Putri, Septiana Rizqi; Angela, Deni (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
This research aims to find out more about the challenges and obstacles to democratization in Yogyakarta and how the role of political actors plays in building a healthy democracy. The research approach used is a qualitative approach, with descriptive research types and data collection methods through secondary data in the form of published works, such as books, journals and articles. The author uses data analysis techniques in three processes, namely understanding the perspective of the original subject under study, understanding the situation of the subject under study related to the research topic, and analyzing events that occur based on the condition of the subject related to the topic to be able to interpret the broader meaning of the data. The research results state that feudalism and identity politics can hinder total democracy in Indonesia. Not to mention the dilemma of implementing democracy as a whole or preserving local culture which in fact will destroy democracy, one of which is the regional leader of the sultan who is not elected by election. Therefore, continuous efforts are needed by providing political education, political class, and protecting marginal groups as a form of instilling democratic values.